2021
DOI: 10.1021/acsami.1c16257
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Labeling to Investigate Nanopatterning Processes in Extreme Ultraviolet Lithography

Abstract: Extreme ultraviolet (EUV) lithography uses 13.5 nm light to reach the sub-20 nm resolution. However, the process of pattern formation induced by this high-energy light is not wellunderstood. In this work, we provide an inorganic EUV photoresist with fluorescence properties by introducing a carbazole derivative as a ligand, and we study its effect on the patterning process. Using the fluorescence properties, changes in the emission of the material after EUV exposure could be tracked by means of spectroscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Lithography technology has played a critical role in the semiconductor industry [ 1 , 2 , 3 , 4 , 5 ], enabling the miniaturization of devices and the reduction in semiconductor nodes from 10 mm to 7 nm over the past 50 years [ 6 , 7 ]. Photoresist is one of the key materials for nanofabrication in lithography, and the patterning generated by lithography acts as an etch-resistant agent to protect the silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Lithography technology has played a critical role in the semiconductor industry [ 1 , 2 , 3 , 4 , 5 ], enabling the miniaturization of devices and the reduction in semiconductor nodes from 10 mm to 7 nm over the past 50 years [ 6 , 7 ]. Photoresist is one of the key materials for nanofabrication in lithography, and the patterning generated by lithography acts as an etch-resistant agent to protect the silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of metal‐based photoresists in resolution, sensitivity, and line edge roughness, researchers adjusted ratios of metal and oxo to optimize the optical lithography pattern. Thakur et al reported high metal–ligand ratio in zinc‐based hydroxyl nucleus with high resolution to improve absorbance ability of sensitivity and give small molecular size; thus, as‐synthesized Zn‐oxo clusters with a Zn 4 O shell achieved a 22‐nm line pattern at 20 mJ cm −2 27–30 . To confirm the influence of metal–ligand ratio, Zhang et al investigated the surface ligand effect of non‐alkyl Sn 10 ‐oxo clusters and found that a higher Sn:O ratio brought better resolution and the prepared resist obtained a sub‐50 nm resolution at a dose of 100 μC cm −2 in EBL 12 …”
Section: Introductionmentioning
confidence: 99%
“…However, the metal–oxo ratio is not the sole factor that influences photoresist performance in metal–oxo clusters; ligands with various substituted groups such as −F/Cl/Br/I atom, −CF 3 , −NO 2 , and even a molecular with π‐system 30 have different influences on the resolution and sensitivity. Xu and his colleagues synthesized two double‐shell zinc‐oxo clusters by the monofunctional/different ligands of m ‐methyl benzoic acid and benzoic acid and the existence of m ‐methyl gave a twist structure, declining the line edge roughness and achieving 15 nm resolution at a dose of 35 mJ cm −2 under EUV, a better result than un‐twist structure without m ‐methyl 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Another key factor is the solubility of Zr6O4 in development solvents [17] . To overcome these problems related to Zr6O4 cluster photoresists, several attempts have been made to meet the requirements of EUV lithography including the use of different ligands, [17] multiple ligands, [3b] fluorinated ligands, [4d] and fluorescent labelled ligands [4e] …”
Section: Introductionmentioning
confidence: 99%